Rates of use of community treatment orders in Australia. (May 2019) - Light, Edwina
Abstract: Objectives: The variable and changing rates of use of involuntary community treatment orders (CTOs) in the treatment of people living with mental illness are not well-documented or well understood. This new study sought to determine contemporary rates of use in Australia, where local jurisdictions were previously shown to have varied and shifting rates of use that were high by world standards. Methods: Australian state and territory mental health review tribunals, health departments, and/or offices of the chief psychiatrist were surveyed for the most recent published annual data on the total number of individual people placed on a CTO and/or the total number of CTOs made. Findings: Contemporary rates of CTO use in Australia range from 40.0 per 100, 000 population (in Western Australia) to 112.5 per 100, 000 (in South Australia). Since the last national survey, the rates of people subject to CTOs fell into in two jurisdictions (Victoria and Western Australia). However, rates of CTOs made were higher than previous figures in all jurisdictions reporting data. Use of CTOs in Australia varies considerably within and between jurisdictions. Conclusions: Australian jurisdictions continue to use CTOs at high and varying rates, despite unresolved questions about their role and impact. Transparency and accountability around their use would be improved by regular and nationally uniform public reporting of CTO data. Further research into how and why CTOs are used may also provide opportunities to respond to factors driving their use and thereby reduce the use of coercion in mental health care.